Porter Diamond Model and Internationalization of Fintechs - Nahidah Naser (Financial Markets, Institutions and Risks)
This paper relies on Porter Diamond model to explain how and why specific digital financial inclusion is the main driver for the internationalization of Fintechs. Porter’s Diamond model can be used to weigh the importance of using specific digital financial inclusion as key factors for the internationalization of Fintechs. Second, analyze how the competition of using specific digital financial inclusion is a secondary driver for Fintechs entering the global market. Fintechs keep disrupting the incumbent financial system and stability worldwide. Moreover, culture, population, new technology, micro and macro conditions in new markets, data protection, transparency, poverty, regulations, and policies could bring Fintechs and their digital financial inclusion to the rest of the world. Such rapid shift may threaten financial stability through excessive demands on specific digital financial inclusion than others locally and globally, without thoroughly examining the accumulated risks with the absence of particular regulation policies such as data and consumer protection, personal identifiable information (PII), cyber hygiene, and technology controls locally and cross-country resilience, collaboration, information sharing, cybercrimes, money laundry, consumer overleveraging, among others on internationalization Fintechs and their impact on financial stability. Moreover, Fintechs compete with traditional banks and other financial institutions by providing digital banking services, especially in the payments, transfers, loans, and lending sectors. However, due to the lack of transparency data gathering, supervisions and regulations of Fintechs, policies, privacy, cybercrimes, the impact of Fintechs on the financial market and economic stability are yet to be thoroughly examined and evaluated. A literature review on Fintechs and their digital financial inclusion are needed to explore Fintechs and the importance of some selected studies on Fintechs.